Role of Academia in the Life of an Academic City: a Case Study of Poznań, Poland - Stanowicka, Agnieszka (Olsztyn Economic Journal, 2022)
The aim of this study has been to evaluate how a city-academia cooperation model functions, using the city of Poznań as a case for this study. Several benefits were identified from having a college or university seated in a city, for instance: stimulation of the city’s economic growth and development and of its cultural life, positive influence on the labour market, shaping a positive image of the city. For these reasons, the city authorities have been making efforts to attract students to Poznań, to sustain their interest in the city while in academia, and to retain the graduates in the city. It is highly probable that the cooperation model identified in Poznań will work in other academic centres, generating a number of development benefits.